Exploring the prognostic implications of programmed death-ligand 1 expression in canine nodal lymphoma: Insights from surface membrane expression, transcript amount and plasmatic levels - Alessandra Ubiali; Luiza Cesar Conti; Raffaella De Maria; Paola Emanuela Maria Dall'Ara; Laura Marconato; Roberta Ferrari; Damiano Stefanello; Maria Amati; Luca Aresu; Fulvio Riondato; Valeria Martini (Research in Veterinary Science, 2026)

Nodal lymphatic mapping in 22 dogs bearing solid malignant tumors and enlarged regional lymph nodes: A descriptive study (2022–2025) - Elisa Maria Gariboldi; Alessandra Ubiali; Roberta Ferrari; Luigi Auletta; Donatella De Zani; Davide Danilo Zani; Francesco Ferrari; Federica Alessandra Brioschi; Paola Roccabianca; Chiara Giudice; Valeria Grieco; Camilla Recordati; et al. (The Veterinary Journal, 2026)

Antarctic threats: anthropogenic microfibers and plasticizers in the scallop Adamussium colbecki from the Ross Sea - Emma Ferrari; Maria Vittoria Barbieri; Roberta Russo; Aleix Balasch García; Valentina Ferrari; Silvia Simonetti; Giovanni Birarda; Lisa Vaccari; Elisa Bergami; Ethel Eljarrat; Ilaria Corsi (Environmental Research, 2026)

Double emulsion with improved stability for Lactobacillus acidophilus encapsulation in a liquid formulation - Chiara Bufalini; Pier Francesco Ferrari; Junyang Li; Roberta Campardelli (Journal of Food Engineering, 2025)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Stabilization of microbial strains in long-lasting double emulsions as a new strategy for liquid biofertilizer formulation - Pier Francesco Ferrari; Chiara Bufalini; Roberta Campardelli; Anna Brondolo; Enrico Ercole; Domenico Palombo; Patrizia Perego (Food and Bioproducts Processing, 2024)

Short-chain fatty acids modulate the IPEC-J2 cell response to pathogenic E. coli LPS-activated PBMC - Melania Andrani; Luca Ferrari; Paolo Borghetti; Valeria Cavalli; Elena De Angelis; Francesca Ravanetti; Eleonora Dall'Olio; Paolo Martelli; Roberta Saleri (Research in Veterinary Science, 2024)

Osmolarity modulates the de-differentiation of horse articular chondrocytes during cell expansion in vitro: implications for tissue engineering in cartilage repair - Elena De Angelis; Amelia Barilli; Roberta Saleri; Bianca Maria Rotoli; Francesca Ravanetti; Francesca Ferrari; Luca Ferrari; Paolo Martelli; Valeria Dall’Asta; Paolo Borghetti (Veterinary Research Communications, 2023)

Effect of an organic acid blend in Nile tilapia growth performance, immunity, gut microbiota, and resistance to challenge against francisellosis - Vanessa Gomes da Silva; Leonardo Mantovani Favero; Raffaella Menegheti Mainardi; Natália Amoroso Ferrari; Roberta Torres Chideroli; Giovana Wingeter Di Santis; Felipe Pinheiro de Souza; Arthur Roberto da Costa; Daniela Dib Gonçalves; Waldo G. Nuez-Ortin; Maria Mercè Isern-Subich; Admilton Gonçalves de Oliveira-Junior; et al. (Research in Veterinary Science, 2023)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Species diversity, spatial distribution, and assemblages of zooplankton within the Strait of Magellan in austral summer - Giacomo Zagami; Tarcisio Antezana; Ireneo Ferrari; Antonia Granata; Raffaella Sitran; Roberta Minutoli; Letterio Guglielmo (Polar Biology, 2011)

Mutant Prevention Concentration (MPC) of Ciprofloxacin Against Salmonella enterica of Epidemic and Poultry Origin - Rafaela Ferrari; Marciane Magnani; Roberta Barreiros Souza; Maria Cristina Bronharo Tognim; Tereza Cristina Rocha Moreira Oliveira (Current Microbiology, 2011)